Partnership and its role in achieving immune Altnzimihdrash analytical sample of the views of the managers of the industrial sector - yusef hajayem altaee (Iraqi Journal for Administrative Sciences, 2024)
Aaguetsad advantage of being a capitalist economy bubbles and crises, has gone through many crises (crisis, recession, boom), and this crisis was caused by the adoption of fiscal and monetary policies wrong by the academic community at the time and economic fallacies efficient market hypothesis and the reduced role of central banks in the oversight of the banking credit crisis conditions and forecast Ba (a recession - boom) and because of speculation in the financial sector based on the paper-based transactions, especially in the sectors of banking and real estate recently adopted as a basis to lead the process of economic growth at the expense of the real economy (real), thus creating a gap between the real sector and financial support (placebo) and the 2008 financial crisis happened, The recent financial crisis has affected the countries, developing and developed countries was a deficit in the budget and financial bankruptcy of financial institutions and companies large and giant and low functioning of financial markets and stock exchanges, have been encountered by several means, including the infusion of funds and liquidity of these insolvent institutions, and adoption of policies such as arbitrarily raising interest rates until the recent nationalization.